2009
DOI: 10.2340/16501977-0444
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to fatigue in women and men with early rheumatoid arthritis: The Swedish TIRA study

Abstract: Although this study does not permit conclusions to be drawn about causal directions, statistical relationships may be related to clinical conceptions about causation: when disease activity can be significantly reduced by pharmacological treatment this may have a positive effect on fatigue. Specific treatment with respect to the mentioned disability aspects that are related to fatigue is also a clinically reasonable strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 32 publications
0
34
0
1
Order By: Relevance
“…However, those clinical response studies do not examine fatigue response directly, and we have previously shown that female sex is associated with greater odds of improvement in fatigue (21). We suggest that because women report more fatigue than men (10,19,40,49), they have a greater capacity for change in this symptom.…”
Section: Discussionmentioning
confidence: 96%
“…However, those clinical response studies do not examine fatigue response directly, and we have previously shown that female sex is associated with greater odds of improvement in fatigue (21). We suggest that because women report more fatigue than men (10,19,40,49), they have a greater capacity for change in this symptom.…”
Section: Discussionmentioning
confidence: 96%
“…Women had slightly higher levels of fatigue than men even after correction for disease activity, whereas PaGl and pain were similar between the sexes. Other studies have also reported more fatigue in women than in men [20,21,32], but the clinical importance has been debated as the difference is small and not consistently significant [19].…”
Section: Discussionmentioning
confidence: 98%
“…Severe fatigue may occur in more than 40 % of the patients [16] and is as common and severe as pain and is considered harder to manage than pain [17]. On the other hand, in crosssectional studies, pain has almost universally been identified to be one of the most important predictors of fatigue [16,[18][19][20][21]. Pain has also been found to be the major contributor to one of the most commonly used patient-reported outcome: PaGl [22].…”
Section: Introductionmentioning
confidence: 98%
“…In the present study, the women had a higher fatigue score, pain score, and RA disease activity (16)(17)(18). Although women had a lower ADL score, clinical and functional remission were reported, and there were no significant differences between women and men for radiographic findings and CRP (19)(20)(21).…”
Section: Discussionmentioning
confidence: 66%